Effects of winter pulsed warming and snowmelt on soil nitrogen cycling in agricultural soils: A lysimeter study - Green, Danielle; Rezanezhad, Fereidoun; Jordan, Sean; Wagner-Riddle, Claudia; Henry, Hugh A. L.; Slowinski, Stephanie; Van Cappellen, Philippe (Frontiers in Environmental Science, 2022)
In cold regions, climate change is expected to result in warmer winter temperatures and increased temperature variability. Coupled with changing precipitation regimes, these changes can decrease soil insulation by reducing snow cover, exposing soils to colder temperatures and more frequent and extensive soil freezing and thawing. Freeze-thaw events can exert an important control over winter soil processes and the cycling of nitrogen (N), with consequences for soil health, nitrous oxide (N2O) emissions, and nearby water quality. These impacts are especially important for agricultural soils and practices in cold regions. We conducted a lysimeter experiment to assess the effects of winter pulsed warming, soil texture, and snow cover on N cycling in agricultural soils. We monitored the subsurface soil temperature, moisture, and porewater geochemistry together with air temperature, precipitation, and N2O fluxes in four agricultural field-controlled lysimeter systems (surface area of 1 m2 and depth of 1.5 m) at the University of Guelph’s Elora Research Station over one winter (December 2020 to April 2021). The lysimeters featured two soil types (loamy sand and silt loam) which were managed under a corn-soybean-wheat rotation with cover crops. Additionally, ceramic infrared heaters located above two of the lysimeters were turned on after each snowfall event to melt the snow and then turned off to mimic snow-free winter conditions with increased soil freezing. Porewater samples collected from five depths in the lysimeters were analyzed for total dissolved nitrogen (TDN), nitrate (NO3-), nitrite (NO2-), and ammonium (NH4+). N2O fluxes were measured using automated soil gas chambers installed on each lysimeter. The results from the snow removed lysimeters were compared to those of lysimeters without heaters (with snow). As expected, the removal of the insulating snow cover resulted in more intense soil freeze-thaw events, causing increased dissolved N loss from the lysimeter systems as N2O (from the silt loam system) and via NO3- leaching (from the loamy sand system). In the silt loam lysimeter, we attribute the freeze thaw-enhanced N2O fluxes to de novo processes rather than gas build up and release.